Exposing Zn(002) Texture with Sucralose Additive for Stable and Dendrite-Free Aqueous Zinc-Ion Batteries - Tao, Feiyu; Ren, Yingke; Mo, Li’e; Wang, Yifan; Huang, Yang; Zhang, Hong; Shi, Chengwu; Li, Zhaoqian; Liu, Jiaqin; Chen, Lei; Hu, Linhua; Wu, Yucheng (Nano-Micro Letters, 2026)
Aqueous zinc-ion batteries (AZIBs) are currently confronted with the challenge of achieving long-term cyclic stability under high current densities. This issue is primarily attributed to the excessive growth of dendrites and the occurrence of significant side reactions. Herein, sucralose (SCL), as an electrolyte additive, has been used to promote the exposure of the Zn(002) texture. The introduction of SCL can adjust the Zn2+ nucleation and diffusion along different crystal facets, promoting the exposure of the Zn(002) texture. By substituting water molecules in the [Zn(H2O)6]2+, SCL reconfigures the hydrogen bond network in the electrolyte, reconstructing the solvation structure and suppressing the hydrogen evolution reaction. Consequently, the Zn//Zn symmetric battery exhibits long-term cycling stability of over 4900 h at 1 mA cm−2–1 mAh cm−2. Even at a harsh condition of 30 mA cm−2–30 mAh cm−2 (DOD = 73.3%), it can stably cycle for 171 h. The CE of the Zn//Cu half battery reaches 99.61% at 0.2 mA cm−2 with 0.2 mAh cm−2. Employing the optimized electrolyte, after 500 cycles, a high specific capacity of 420 mAh g−1 can be retained for the NH4V4O10//Zn full battery at 500 mA g−1, corresponding to a capacity retention of 90.7%. Highlights: 1 Sucralose (SCL) has been unveiled as an electrolyte additive to promote the exposure of the Zn(002) texture. 2 SCL has been verified to disrupt the solvation structure around zinc ions and reduce water activity on Zn anode. 3 After adding SCL additives, Zn//Zn battery achieves the cycling lifespan of 171 h at 30 mA cm−2–30 mAh cm−2 (DOD = 73.3%). Zn//Cu battery achieves a high Coulombic efficiency of 99.61% at 0.2 mA cm−2 with 0.2 mAh cm−2.